PERTANGGUNGJAWABAN PENYIDIK KEPOLISIAN REPUBLIK INDONESIA DALAM TINDAKAN SALAH PENANGKAPAN TERHADAP PELAKU TINDAK PIDANA DALAM HUKUM PIDANA INDONESIA - Indah Rezeki Manurung; Erdianto Effendi; Ferawati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
One of the arrests is the mistake or negligence of the investigator indetermining the offender. The phenomenon of cases of wrongful catch is evidenceof weak performance of law enforcement officers and this should be accounted forreferring to the professionalism as law enforcement.This type of research can be classified with the type of normative juridicalresearch, because in this study the authors directly synchronize the law by usingthe normative approach focused on library research. This study analyzes thelegislation concerning the accountability of Polri investigators who have miscaughtwhen carrying out the duties and the cause of the wrong action of arrestby the investigator.From the results of this study there are some things that concluded theauthor. First, the occurrence of the victim of the arrest due to the lack ofunderstanding and the implementation of the investigator against the principle ofpresumption of innocence and the Criminal Procedure Code, the investigator usesa way contrary to the law to investigate the suspect by force or use violence toobtain information and recognition of the suspect, making BAP is far from actualthis matter may be punished and prosecuted in pre-trial shall be imposed withArticle 52, Article 333, Article 334, Article 351 of the Criminal Code. Secondly,the responsibility of the police investigator is divided into two, namely thematerial responsibility, namely the sanction of apology and the immaterialresponsibility, namely the sanction in the form of the obligation of re-education inthe institution of the police education.Keywords: Accountability - Investigators - False Arrest